An Exploratory Study of Simulations for Leadership Development in the Principal Pipeline - M. Elizabeth Azukas; Sara Dexter; David Gibson (Education Sciences, 2025)
This article examines the integration of digital simulations as a tool for strengthening leadership development across the four phases of the principal pipeline—recruitment, preparation, induction, and in-service professional development. Set in the context of a partnership between a preparation program and district-based leadership development, the study investigated to what extent simulations could bridge gaps along the pipeline to create a more coherent and continuous approach to principal development. The findings suggest that sims help prospective leaders develop a more nuanced understanding of school leadership, enhance decision-making skills for candidates in preparation programs, and provide targeted support for new and experienced administrators.